2009
DOI: 10.1002/jso.21256
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of gastric outlet obstruction on the oncologic and surgical outcomes of radical surgery for carcinoma of the distal stomach

Abstract: The presence of GOO is an independent prognostic factor after radical surgery for advanced distal gastric cancer and provide additional information for identifying patients at higher risk of recurrence and pattern of recurrence during follow-up. Radical surgery in patients with GOO can be performed with acceptable morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 28 publications
3
8
0
Order By: Relevance
“…Tumor size more than 5 cm [15] and pathological T4 in our series predicted increased morbidity. Gastric outlet obstruction was not reported to be associated with increased incidence of high grade postoperative complications [35]. Large tumors and presence of gastric outlet obstruction can be associated with cancer cachexia and nutritional problems which account for significant morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor size more than 5 cm [15] and pathological T4 in our series predicted increased morbidity. Gastric outlet obstruction was not reported to be associated with increased incidence of high grade postoperative complications [35]. Large tumors and presence of gastric outlet obstruction can be associated with cancer cachexia and nutritional problems which account for significant morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Hu et al [30] reported a postoperative complication rate of 10.2% in 1,184 patients with advanced gastric cancer. The most common major complication in the LDG group was pancreatic fistula, which tends to reflect surgical inexperience and a learning curve [34] . Pancreatic fistulas occurred in 3 patients undergoing LDG in 2010, the year we started performing D2 lymphadenectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Whether obstruction is associated with a more advanced disease stage or impedes food intake, which may contribute to a poor outcome, remains open to question. In a retrospective study of patients who underwent radical surgery for distal cancers, gastric outlet obstructions significantly reduced the survival time from 50.8 to 30.6 months (P=0.001) [22]. …”
Section: Discussionmentioning
confidence: 99%